DISASTER VICTIM IDENTIFICATION (DVI) TRAINING FOR MEDICAL STUDENT - Taufik Suryadi Ismail; Kulsum Binti Syarifudin (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Disaster victim identification (DVI) is a process of identifying the victim who died due to the disaster. Deaths due to disasters can be classified as victims of open disasters and victims of closed disasters. In the open disasters the process of identification is more difficult. Based on regulation of law in Indonesia, the identification is intended to fulfil human rights to identity, dignity and social status, autonomy rights such as inheritance, marital status, religion, insurance or other legal and social issues. Aims: The purpose of this curriculum study is to provide an overview of the DVI training process for medical students. Curriculum Discussion: Given the importance of the identification process it is necessary to be included in the medical education curriculum. The DVI training to identify victims of mass disasters uses the DVI Interpol standard. Faculty of Medicine Universitas Syiah Kuala has conducted training and simulations of DVI for medical student since 2009 until 2019. A total of 1995 students in this period have participated in the training. The DVI training for medical students is very needed as an addition to the competence of doctors in the field of disaster management. Conclusion: By joining this training, medical students have sufficient medical skills to assist in the process of DVI.